Ethics review of COVID-19 human challenge studies: a joint HRA/WHO workshop - Williams, E; Craig, K; Chiu, C; Davies, H; Ellis, S; Emerson, C; Jamrozik, E; Jefford, M; Kang, G; Kapulu, M; Kolstoe, SE; Littler, K; et al. (Elsevier, 2022)
This report of a joint World Health Organization (WHO) and United Kingdom (UK) Health Research Authority (HRA) workshop discusses the ethics review of the first COVID-19 human challenge studies, undertaken in the midst of the pandemic. It reviews the early efforts of international and national institutions to define the ethical standards required for COVID-19 human challenge studies and create the frameworks to ensure rigorous and timely review of these studies. This report evaluates the utility of the WHO's international guidance document Key criteria for the ethical acceptability of COVID-19 human challenge studies (WHO Key Criteria) as a practical resource for the ethics review of COVID-19 human challenge studies. It also assesses the UK HRA's approach to these complex ethics reviews, including the formation of a Specialist Ad-Hoc Research Ethics Committee (REC) for COVID-19 Human Challenge Studies to review all current and future COVID-19 human challenge studies. In addition, the report outlines the reflections of REC members and researchers regarding the ethics review process of the first COVID-19 human challenge studies. Finally, it considers the potential ongoing scientific justification for COVID-19 human challenge studies, particularly in relation to next-generation vaccines and optimisation of vaccination schedules. Overall, there was broad agreement that the WHO Key Criteria represented an international consensus document that played a powerful role in setting norms and delineating the necessary conditions for the ethical acceptability of COVID-19 human challenge studies. Workshop members suggested that the WHO Key Criteria could be practically implemented to support researchers and ethics reviewers, including in the training of ethics committee members. In future, a wider audience may be engaged by the original document and potential additional materials, informed by the experiences of those involved in the first COVID-19 human challenge studies outlined in this document.